Production of poly (3-hydroxybutyrate-co-4-hydroxybutyrate) by Burkholderia sacchari using wheat straw hydrolysates and gamma-butyrolactone - Cesário, M. Teresa (2014)
"Burkholderia sacchari DSM 17165 is able to grow and produce poly(3-hydroxybutyrate) both on hexoses and pentoses. In a previous study, wheat straw lignocellulosic hydrolysates (WSH) containing high C6 and C5 sugar concentrations were shown to be excellent carbon sources for P(3HB) production. Using a similar feeding strategy developed for P(3HB) production based on WSH, fedbatch cultures were developed aiming at the production of the copolymer P(3HB-co- 4HB) (poly(3-hydroxybutyrate-co-4-hydroxybutyrate)) by B. sacchari. The ability of this strain to synthesize P(3HB-co-4HB) was first shown in shake flasks using gammabutyrolactone (GBL) as precursor of the 4HB units. Fed-batch cultures using glucose as carbon source (control) and GBL were developed to achieve high copolymer productivities and 4HB incorporations. The attained P(3HBco- 4HB) productivity and 4HB molar % were 0.7 g/(L·h) and 4.7 molar %, respectively. The 4HB incorporation was improved to 6.3 and 11.8 molar % by addition of 2 g/L propionic and acetic acid, respectively. When WSH were used as carbon source under the same feeding conditions, the values achieved were 0.5 g/(L·h) and 5.0 molar %, respectively. Burkholderia sacchari, a strain able to produce biopolymers based on xylose-rich lignocellulosic hydrolysates, is for the first time reported to produce P(3HB-co-4HB) using gamma butyrolactone as precursor."